ANALISIS VALUE FOR MONEY PADA KINERJA KEUANGAN DINAS LINGKUNGAN HIDUP KABUPATEN ROKAN HULU - Putra , M. Fauzan; Nursida , Nina (Journal Of Islamic Finance And Accounting Research, 2023)
This study aims to analyze the performance accountability of the Rokan Hulu District Environmental Office using the principle of value for money. The type of research used is qualitative research. The collection technique obtained was in the form of Performance Reports of Government Agencies at the Rokan Hulu Regency Environmental Service for 2020 and 2021. The results of this study indicate that in 2020 economical calculations with a ratio value of 72% are categorized as economical, efficient calculations with a ratio value of 131% are categorized as efficient, and effectiveness calculations with a ratio value of 93% are categorized as ineffective. In 2021 economic calculations with a ratio value of 93.32% are categorized as economical, efficient calculations with a ratio value of 101.77% are categorized as efficient, and effectiveness calculations with a ratio value of 59% are categorized as ineffective. Thus the performance of the Rokan Hulu Regency Environmental Service in 2020 and 2021 in terms of economic elements, efficiency and effectiveness has not fulfilled the principle of value for money.